2008
DOI: 10.1002/jcb.21784
|View full text |Cite
|
Sign up to set email alerts
|

Differential expression of the two distinct replication protein A subunits from Cryptosporidium parvum

Abstract: Apicomplexan parasites differ from their host by possessing at least two distinct types (long and short) of replication protein A large subunits (RPA1). Different roles for the long and short types of RPA1 proteins have been implied in early biochemical studies, but certain details remained to be elucidated. In the present study, we have found that the Cryptosporidium parvum short-type RPA1 (CpRPA1A) was highly expressed at S-phase in parasites during the early stage of merogony (a cell multiplication process … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
7
0

Year Published

2009
2009
2017
2017

Publication Types

Select...
5
2

Relationship

3
4

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 31 publications
1
7
0
Order By: Relevance
“…Only 31 or 27 genes stayed either up- or down-regulated expressions, respectively, in both 0.5 h and 5 h groups (clusters 1 and 9), in which only a small number of genes could be functionally categorized. Among them, genes encoding a DNA replication licensing factor (cgd2_1250) and DNA polymerase epsilon subunit (cgd8_1240) remained up-regulated in both 0.5 h and 5 h groups, which suggested that DNA repair machinery in the oocysts was activated soon after UV-irradiation, and lasting for >5 h. The data were generally in agreement with our previous observations on a select panel of DNA repair-associated genes in the parasite in response to UV-irradiation [31]. Additionally, the long-lasting up-regulated expressions of γ-tubulin and a microtubule-associated protein indicated that the cytoskeletal elements underwent substantial rearrangements in the parasite, probably as needed for transporting and recycling the damaged macromolecules and cellular components.…”
Section: Resultssupporting
confidence: 90%
“…Only 31 or 27 genes stayed either up- or down-regulated expressions, respectively, in both 0.5 h and 5 h groups (clusters 1 and 9), in which only a small number of genes could be functionally categorized. Among them, genes encoding a DNA replication licensing factor (cgd2_1250) and DNA polymerase epsilon subunit (cgd8_1240) remained up-regulated in both 0.5 h and 5 h groups, which suggested that DNA repair machinery in the oocysts was activated soon after UV-irradiation, and lasting for >5 h. The data were generally in agreement with our previous observations on a select panel of DNA repair-associated genes in the parasite in response to UV-irradiation [31]. Additionally, the long-lasting up-regulated expressions of γ-tubulin and a microtubule-associated protein indicated that the cytoskeletal elements underwent substantial rearrangements in the parasite, probably as needed for transporting and recycling the damaged macromolecules and cellular components.…”
Section: Resultssupporting
confidence: 90%
“…2A). Previous studies indicated that DNA replication occurs near this time in type I meronts (Rider and Zhu, 2008). Examination of BrdU that was incorporated into DNA during genome replication further revealed that CpHDAC3 was associated with recently replicated parasite DNA (Fig.…”
Section: Resultsmentioning
confidence: 92%
“…The expression specificity of Rlp1 and Rlp2 suggests that they and Teb3 could function together specifically in mated cells. The complexity of RPA and RPA-like complexes in Tetrahymena provides new insights and opportunities to understand the function of alternative RPA subunits, which, based on genome sequencing, appear widespread across organisms ranging from apicomplexan parasites to plants to mammals (41)(42)(43).…”
Section: Proteinmentioning
confidence: 99%
“…Curiously, the same proteins make different functional contributions to different heterotrimers. Understanding the complexity of RPA and RPA-like complexes in Tetrahymena provides a precedent for studies of alternative RPA subunits in other organisms, including humans (41)(42)(43).…”
mentioning
confidence: 99%